Mi azaroso camino hacia la historia andina - Sánchez-Albornoz, Nicolás (2020)
The following autobiographic note of the renowned historian Nicolás Sánchez-Albornoz illustrates how life’s different vicissitudes carried him to the field of Andean history. In virtue of his book Trabajo y migración indígenas en los Andes coloniales’ presentation, this recount of the past invites to rethink the historian vocation. It tells us that the specialization pursued will not always be due to genuine personal or academic interests, but to different political, geographical, and temporal circumstances.